2014
DOI: 10.3892/or.2014.3052
|View full text |Cite
|
Sign up to set email alerts
|

miR-7 inhibits the invasion and metastasis of gastric cancer cells by suppressing epidermal growth factor receptor expression

Abstract: The present study profiled differentially expressed microRNAs (miRs) in gastric cancer cell lines and then investigated miR-7 expression in gastric cancer tissue specimens and the effects of miR-7 on the growth, invasion and metastasis of gastric cancer cells and the underlying molecular events. A microRNA microarray was used to profile differentially expressed miRNAs in human gastric cancer cell lines relative to a normal stomach mucosal epithelial cell line. The miRNA miR-7 was selected for further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 53 publications
2
59
0
Order By: Relevance
“…Comparative microarray profiling of gastric cancer and normal cell lines revealed differential expression of 14 miRNAs, including miR-21, miR-26b and miR-30b that are upregulated and 19 miRNAs, including let-7i, miR-7, miR-622 were downregulated in gastric cancer [27]. Zhang et al [28] demonstrated that overexpression of miR-21 in the gastric cancer cell line, AGS enhanced the proliferation and invasive ability of cells.…”
Section: Mir-21 As a Oncogenic Biomarker In Gastric Cancermentioning
confidence: 98%
“…Comparative microarray profiling of gastric cancer and normal cell lines revealed differential expression of 14 miRNAs, including miR-21, miR-26b and miR-30b that are upregulated and 19 miRNAs, including let-7i, miR-7, miR-622 were downregulated in gastric cancer [27]. Zhang et al [28] demonstrated that overexpression of miR-21 in the gastric cancer cell line, AGS enhanced the proliferation and invasive ability of cells.…”
Section: Mir-21 As a Oncogenic Biomarker In Gastric Cancermentioning
confidence: 98%
“…Another two studies reported that miR-7 was expressed at a high level during human pancreatic islet development [10,17] . For malignancy, it has been demonstrated that miR-7 is downregulated in cancer tissue of digestive malignancies such as GC [18][19][20] , CRC [21,22] and hepatocellular carcinoma (HCC) [23] by comparison with normal tissues, suggesting that it acts as a suppressor. A similar conclusion was drawn in a study of hydroxycamptothecin-resistant GC cells [24] .…”
Section: Expression Of Mir-7mentioning
confidence: 99%
“…MiR-7 suppresses GC cell invasion and metastasis both in vitro and in vivo by targeting the miR-7/insulin-like growth factor 1 receptor/Snail axis, which shows its EMT function and suggests that it can act as a therapeutic biomarker to prevent GC metastasis [18] . Xie et al [19] demonstrated that restoration of miR-7 significantly inhibited tumor cell viability, invasion and migration by suppressing EGFR expression. These results suggest that targeting miR-7 is a potential therapeutic option for GC (Figure 1).…”
Section: Gcmentioning
confidence: 99%
“…To date, ~2,000 human miRNAs have been identified, which are involved in the regulation of biological processes, including proliferation, apoptosis, migration and differentiation (8). Several miRNAs have been implicated as oncogenes or as tumor suppressors, and are aberrantly expressed in various types of cancer, including RCC (9)(10)(11)(12). Previous studies have demonstrated, through transfection with pre-miR-509-3p in vitro, that miR-509-3p is downregulated in RCC, which is associated with cell proliferation and migration in 786-O RCC cells.…”
Section: Introductionmentioning
confidence: 99%